Well-trained endurance runners` foot contact patterns: Barefoot vs. shod condition - Mosqueira-Ouréns, M.; Muñoz-Pérez, I.; Tuimil, J. L.; Saleta-Cobos, M.; Varela-Sanz, A. (International Journal of Sports Medicine, 2023)
We aimed to investigate the initial foot contact and contact time in experienced endurance runners at individualized speeds, in running shoes and barefoot. Forty-eight participants (33.71±7.49 y, 70.94±8.65 kg, 175.07±7.03 cm, maximum aerobic speed 18.41±1.54 km.h-1) were distributed into three groups according to athletic performance: highly-trained runners, middle-trained runners, and control group. An incremental running test until exhaustion was performed for assessing maximum aerobic speed. After=24 h of recovery participants randomly walked and ran, barefoot and in running shoes, over a pressure plate at ~4.7 km.h-1 and 85% of the maximum aerobic speed, respectively. They wore the same model of running shoes with homogeneous lacing pattern. A rearfoot strike was performed by 68.8% and 77.1% of participants when running barefoot and in running shoes, respectively. Considering the tendency to develop a rearfoot strike was lower in the barefoot condition, runners with higher performance may benefit from training in minimalist running shoes because their foot contact pattern could tend towards a non-rearfoot strike. Our results suggest that initial foot contact and contact time are related to running performance and may also be influenced by running shoes.